Rodent pests and their control - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Rodent pests and their control edited by A P Buckle and R H Smith 1994 416pp price UKL49.95 ISBN 85198 829 2 Hbk CAB International, Wallingford Oxon OX10 8DE UK